2021
DOI: 10.3389/fpsyg.2021.712356
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Implicit Attitudes Toward Ethnic Minority Students: A Systematic Review

Abstract: Although instruments to assess implicit attitudes were introduced more than 20 years ago, still there are few studies in the field of education that use them, despite the evidence that teachers with negative implicit attitudes can negatively affect the academic performance of their students. This review aims to summarize the results of studies that investigated the relationship between implicit ethnic attitudes of teachers and achievement of students. The review was conducted according to PRISMA-statement thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 83 publications
(123 reference statements)
1
7
0
Order By: Relevance
“…However, as the focus of attitude assessment has shifted toward the examination of implicit evaluations ( Sritharan and Gawronski, 2010 ), research from the educational field has indicated that teachers show more negative implicit attitudes toward ethnic minority students ( Glock et al, 2020 ). The same results have been found for preservice teachers, who tend to exhibit less favorable implicit attitudes toward ethnic minority students than toward ethnic majority students ( Costa et al, 2021 ). Explicit attitudes are often assessed with self-report measures ( Sritharan and Gawronski, 2010 ); implicit attitudes, however, are calculated from response latencies on tasks involving indirect measurement methods ( Wittenbrink and Schwarz, 2007 ).…”
Section: Implicit Attitudessupporting
confidence: 78%
See 3 more Smart Citations
“…However, as the focus of attitude assessment has shifted toward the examination of implicit evaluations ( Sritharan and Gawronski, 2010 ), research from the educational field has indicated that teachers show more negative implicit attitudes toward ethnic minority students ( Glock et al, 2020 ). The same results have been found for preservice teachers, who tend to exhibit less favorable implicit attitudes toward ethnic minority students than toward ethnic majority students ( Costa et al, 2021 ). Explicit attitudes are often assessed with self-report measures ( Sritharan and Gawronski, 2010 ); implicit attitudes, however, are calculated from response latencies on tasks involving indirect measurement methods ( Wittenbrink and Schwarz, 2007 ).…”
Section: Implicit Attitudessupporting
confidence: 78%
“…The most prominent method for accessing implicit attitudes is the Implicit Association Test (IAT; Greenwald et al, 1998 ), which is used to calculate participants’ reaction times as they make cognitive associations. When applied to teachers’ implicit attitudes, it is assumed that teachers are quicker to assign positive attributes to ethnic majority students and negative attributes to ethnic minority students, the more strongly these concepts are cognitively linked ( Costa et al, 2021 ). Hence, if the targets and attributes are strongly linked, the response latencies are shorter ( Greenwald et al, 1998 ).…”
Section: Implicit Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, studies consistently reveal that educators hold more negative attitudes toward their students from minoritized ethnic‐racial groups compared to their students from non‐minoritized backgrounds (e.g., Peterson et al., 2016). In turn, these beliefs prejudice educators' expectations and evaluations of their students' academic potential, and subsequently undermine the achievement of students from minoritized ethnic‐racial backgrounds (see Costa et al., 2021). Educators' expectations for their students have also been shown to contribute to inequalities between students from lower and higher SES backgrounds (e.g., Sorhagen, 2013), as educators tend to expect less from lower SES students.…”
Section: Introductionmentioning
confidence: 99%